(untitled) (CAHIERS MAGELLANES-NS, 2024)
Internal hernia is protrusion of viscera, largely small bowel through a peritoneal or mesenteric aperture (although not all internal hernias are strictly intraperitoneal).In general, interior hernias may be acquired or else congenital. After surgery or trauma, aberrant mesenteric flaws are created, which leads to acquired internal hernias. Inadequate closure (or dehiscence) of mesenteric defects caused by gastrojejunostomy, liver transplant, colostomy, ileostomy, or colon resection is typically the cause of these. For instance, the defect is typically closed because hernia rates following laparoscopic RYGB (Roux-en-Y gastric bypass) have been described to be as high as 9%. Normal foramen, failure of peritoneal fusion, and unusual peritoneal orifices account for the congenital internal hernias. Considering the bowel loops' topographic distribution, Welch classified internal hernias into 8 types. The various anatomical sites include left and right paraduodenal (mesocolic) hernia, foramen of Winslow hernia (abnormally large foramina), pericecal hernia, transomental hernia, sigmoid-mesocolon-related hernia, transmesenteric hernia, supravesical (abnormally large foramina) and pelvic hernia. The most frequent type of internal hernias, paraduodenal hernias (PDH), are caused by tiny bowel loops entering an aberrant fossa near the duodenum due to improper retroperitoneal anchoring of the mesentery with the parietal peritoneum. There are 2 types of paraduodenal hernia. The small intestine becomes trapped in “the fossa of Landzert, an uncommon congenital peritoneal fossa behind the descending mesocolon, in left PDH, that is more frequent. Located to left of IMV (inferior mesenteric vein) on the abdomen’s left side is the hernial sac. The fossa of Waldeyer, which develops when a portion of the ascending mesocolon fails to fuse with posterior parietal peritoneum, is usually” the cause of right PDH (12). They are related to a nonrotated small intestine. The hernial sac is located to the right of SMA on the right side of abdomen. The common presentation of PDHs is a closed-loop intestinal obstruction. With a mortality rate of 20 to 50 percent, PDH carries a greater than 50% lifetime risk of intestinal infarction and strangulation (11). In some cases, there occurs a spontaneous reduction of partial or complete contents of the internal hernial sac upon laparotomy. Many centers have performed laparoscopic procedures. In our study, we described a case of a left paraduodenal -internal hernia including closed loop obstruction with an impression (obtained while content was inside the orifice) of the constriction ring at ileocecal junction, initially diagnosed at distal ileal stricture. We aim to emphasize the importance of detailed clinical history taking and examination along with interpretation of relevant CT findings which aid in narrowing the diagnosis in cases of small bowel obstruction, the second most prevalent cause of acute abdomen. Thus, with a good preoperative diagnosis and plan, there is less morbidity and improved survival.